Strategic analysis of alignment: CEMARS certification programme and selected carbon initiatives and reporting frameworks - Saynevirta, Seija Helena (2008)
There is a growing urgency of the need for action to mitigate and adapt to climate change and this issue has been rising on the business agenda in the recent years. As companies seek to understand the impact they have on climate change, the importance of understanding and engaging with the supply chain has gained increasing momentum.